2014
DOI: 10.1136/bmjopen-2014-005246
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid factor and anti-CCP do not predict progressive joint damage in patients with early rheumatoid arthritis treated with prednisolone: a randomised study

Abstract: ObjectiveTo analyse if predictors of radiographic progression differ between patients treated with or without prednisolone in early rheumatoid arthritis (RA). Radiographs of hands and feet were assessed using the modified Sharp/van der Heijde score and radiographic progression was defined as an increase in the total Sharp score above 5.8 (the smallest detectable change).DesignProspective, randomised study of patients with early RA.SettingSecondary level of care; six participating centres from southern Sweden; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
2
17
1
Order By: Relevance
“…This was in agreement with the main finding in Grandaunet et al, their study enrolled 238 patients with RA, that Dkk1 levels at baseline were significantly higher (2010 pg/mL) in patients developing per articular bone loss compared with patients without per articular bone loss (1332.2 pg/mL, P<0.05) [25]. There was also negative correlation between s.DKK-1 levels and forearm T-score, lumbar T-score and neck of femur T-score, moreover a difference was found in serum Dkk1 levels between DEXA grading (normal, osteopenic, osteoporotic) but didn't reach a statistical significant level(H=0.91, P>0.05).…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with the main finding in Grandaunet et al, their study enrolled 238 patients with RA, that Dkk1 levels at baseline were significantly higher (2010 pg/mL) in patients developing per articular bone loss compared with patients without per articular bone loss (1332.2 pg/mL, P<0.05) [25]. There was also negative correlation between s.DKK-1 levels and forearm T-score, lumbar T-score and neck of femur T-score, moreover a difference was found in serum Dkk1 levels between DEXA grading (normal, osteopenic, osteoporotic) but didn't reach a statistical significant level(H=0.91, P>0.05).…”
Section: Discussionsupporting
confidence: 92%
“…[15][16][17][18][19][20][21][22][23] It is noteworthy that most of these studies used the Larsen or Sharp method in their radiographic evaluation. Håfström et al, 44 in a prospective study examining the role of RF and anti-CCP based on the radiological progression with the use of the SvdH method in patients with early RA, according to prednisolone use, found that RF and anti-CCP were predictors of radiographic progression only in patients who did not use steroids. Our work also did not establish an association of anti-CCP with structural damage, as assessed by SvdH in established RA cases, which is in accordance with Håfström et al's study, since 87.5% of our patients were still being medicated with prednisone.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the descendants of patients with RA may have increased RF levels, even without exhibiting any RA symptoms, while infections caused by Mycoplasma and Streptococcus can also result in disorders of the autoimmune system, and thus induce RA (17,18). The diagnosis of RA is made based on the clinical symptoms of the patients, X-ray results and RF detection results, and the serum RF level is the only serological indicator of RA (19,20). VCAM-1 is an essential cell adhesion molecule and its expression can be induced by inflammatory cytokines, such as IL-6 and TNF, which participate in the differentiation and development of lymphocytes and are associated with the pathological processes of several diseases, including systemic inflammation, tumor invasion and metastasis, autoimmune diseases and parasitic infections (21,22).…”
Section: Discussionmentioning
confidence: 99%